The state of emotional sphere and personality features in patients with organic brain lesions in a hospital with strict supervision - Jivilova, Jana (Psychiatry, Neurology and Medical Psychology, 2018)
The article presents data on the state of the emotional sphere and personal characteristics of patients with organic brain lesions, who are treated in a hospital with strict supervision. Such information is essential for predicting both the course of the disease and the possible subsequent illegal behavior of these patients, the degree of their public danger. It is established that these patients are distinguished by high rates of personal anxiety and hostility index. In accordance with the results obtained in the course of the study, a system of medical and psychological support of such patients was developed in a hospital with strict supervision using various psychotherapeutic methods. Their volume and sequence are formed taking into account the state of the emotional sphere and personality-characterological features. Targets for restorative therapy and medical and psychological rehabilitation are determined, taking into account the possibilities of pharmacotherapy and psychotherapy.